The Behavioral Speech Acts in the Kurdistan Parliamentary Discussion - پرۆفیسیۆر دکتۆر قەیس كاكل تۆفیق; مامۆستا پەروین عوسمان مستەفا (QALAAI ZANIST JOURNAL, 2019)
This study which is entitled ’The Behavioral Speech Acts in the Kurdistan Parliamentary Discussion; according to Sex’ analyses the behavioral speech acts according to subjects and sex. And that behavioral act is a kind of speech acts, and these acts are linked to those speech acts of psychological state that are issued by the parliament members during their discussion through a number of acts through which they express their feelings. The methodology has taken, in this research, the statistical descriptive approach, and models or data were taken from the Protocols of the Kurdistan Parliament, according to a number of legal projects discussed in the parliamentary sessions during three sessions: the second session of the Parliament (2005_2008) and the third session (2009_2012) and the fourth session (2013-2017). The research is based on statistical principles and the main objective of the research is to access the percentage of the use of speech acts by subject and sex on the one hand and the proportion of behavioral speech acts by sex (male and female).